Electrosorption performance on graphene-based materials: a review - Liu, Yan (2023)
Due to its unique advantages such as flexible planar structure, ultrahigh specific surface area, superior electrical conductivity and electrical double-layer capacitance in theory, graphene has unparalleled virtues compared with other carbon materials. This review summarizes the recent research progress of various graphene-based electrodes on ion electrosorption fields, especially for water desalination utilizing capacitive deionization (CDI) technology. We present the latest advances of graphene-based electrodes, such as 3D graphene, graphene/metal oxide (MO) composites, graphene/carbon composites, heteroatom-doped graphene and graphene/polymer composites. Furthermore, a brief outlook on the challenges and future possible developments in the electrosorption area are also addressed for researchers to design graphene-based electrodes towards practical application.